Bauxite Mining Restoration with Natural Soils and Residue Sands: Comparison of the Recovery of Soil Ecosystem Function and Ground-dwelling Invertebrate Diversity - Mihindukulasooriya Weerasinghe, Dilanka Madusani (Curtin University, 2019)
This thesis investigated the re-establishment of soil ecosystem functions and ground-dwelling invertebrate diversity in a chronosequence of restored sites within two distinctly different restoration projects (mining pits and residue sand storage areas) associated with Alcoa’s bauxite mining operation in Western Australia. Both restoration practices are improving habitat characteristics towards reference sites, but changes to soil ecosystem functions were more rapid in mining than residue restoration with invertebrate seed dispersal lacking in the residue restoration sites.